REFLECTIONS ON THE NOTION OF IMPLICIT FAITH - Wilkins, Jeremy (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2023)
If we affirm that salvation occurs apart from the acceptance of Christian revelation, then either faith is not necessary for salvation, or saving faith occurs apart from the historical transmission of the Gospel. Either conclusion is difficult to reconcile with traditional Catholic doctrines. Let us suppose that it is more congruous to say that faith occurs outside the historical communion of Christ than to say that salvation occurs without faith. There arises a twofold question about the faith that occurs outside a Christian context, namely, how it is related to Jesus Christ, and how it is related to the meanings and values of the context in which it does occur. This article develops some theological categories for approaching this problem, in conversation with Aquinas, Lonergan, and the Catholic doctrinal tradition.